2021
DOI: 10.1088/1755-1315/819/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma boninense control in palm oil plantations using Trichoderma harzianum in various Media

Abstract: Ganoderma boninense is a pathogen that can attack palm oil plants. This fungus can cause death, causing a decrease in the number of stands and palm oil production. One alternative to control Ganoderma boninense in palm oil is using the biological agent; ‘Trichoderma harzianum’. This research aimed to examine the inhibition of T. harzianum in various media on different spear leaves accumulations on G. boninense in palm oil plants. The research was arranged in a factorial randomized block design. The first facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To accommodate these gases, a portion of the internal space in the fermentation tank needs to be reserved. The cow dung is in a loose accumulation state with large internal porosity [32]. To facilitate feeding and material collection, the fermentation tank is equipped with a feed inlet and a discharge outlet on the side and bottom, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To accommodate these gases, a portion of the internal space in the fermentation tank needs to be reserved. The cow dung is in a loose accumulation state with large internal porosity [32]. To facilitate feeding and material collection, the fermentation tank is equipped with a feed inlet and a discharge outlet on the side and bottom, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Different media compositions were evaluated, showing significant effects on spear leaf count, mycelium growth, and root length. The combination of 25% oil palm empty fruit bunches and 75% cow dung compost yielded the best results in reducing spear leaf count, while 50% OPEFB and 50% cow dung compost stimulated root growth [ 277 ]. Endophytic Trichoderma species from North Sumatra, Indonesia, were evaluated for their effectiveness in preventing BSR disease in oil palm nurseries.…”
Section: Research On Disease Management Strategies To Control Basal S...mentioning
confidence: 99%
“…Trichoderma dan Mycorrhizae are biological control agents that have been used for a long time to prevent G. boninense fungal infection in the field. 14 Sukariawan et al 15 reported Trichoderma harzianum in various media was capable to control the Ganoderma disease in OP plantations. In particular, the OP empty fruit bunch and cow dung could act as T. harzianum media as well as a source of soil organic matter.…”
Section: Introductionmentioning
confidence: 99%